Water absorption of epoxy/glass fiber/organo-montmorillonite nanocomposites (eXPRESS Polymer Letters)
The epoxy/glass fiber/organo-montmorillonite (OMMT) nanocomposites were prepared by hand lay up method. In the previous work, the flexural and morphological properties of the epoxy/glass fiber/OMMT were studied. In this work, the epoxy nanocomposites were characterized by X-ray diffraction (XRD), differential scanning calorimetry (DSC) and water absorption tests. The exfoliation of OMMT in epoxy/glass fiber nanocomposites was detected by XRD. DSC results showed that the glass transition temperature (Tg) of epoxy was increased slightly in the presence of OMMT. Water uptake of epoxy was reduced by the addition of glass fiber and OMMT. The decrease of water absorption in epoxy is attributed to the increasing of tortuosity path for water penetration in the epoxy composites by the hybrid of glass fiber and OMMT.